Edukasi Cara Menyikat Dan Menjaga Kesehatan Gigi Yang Benar Pada Anak-Anak Di Desa Bandar Magodang - Khairidatun Nisa; Devi Tri Lestari; Putri Handayani; M. Fahrozi Tanjung; Suci Dahlya Narpila (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Activities are mandatory activities carried out by UIN North Sumatra students, especially at the Faculty of Tarbiyah and Teacher Training. PMM-4 students carry out community service activities in Bandar Magodang Village, Bintang Bayu District. One of the series of activities planned by PMM-4 students is a study house which is attended by the children of Bandar Magodang Village. This study house program aims to help the children of Bandar Magodang Village in brushing and maintaining good and correct dental health. This program is running well, this service activity is carried out through 3 stages, namely planning, implementation and evaluation. The method used in implementing this community service is a qualitative approach. Data were collected before and after the intervention to assess changes in children's knowledge and behavior. The results showed a significant increase in their understanding of the importance of brushing their teeth properly and maintaining dental health in general. The implication of these findings is the importance of ongoing dental health education in rural communities to improve children's dental well-being. This learning house action was completed on 18-19 August 2023 in one of the residents' yards in Bandar City, Bintang Bayu District.